MYO19 is associated with tumor progression, immune evasion, ferroptosis-related signatures in lung squamous cell carcinoma - Zhao, Fang; Chen, Guiying; Pan, Jianfeng; Zhang, Yongxiang; Li, Wei; Niu, Kaifeng; Ma, Hui (Frontiers in Oncology, 2026)
BackgroundLung squamous cell carcinoma (LUSC) is a highly aggressive malignancy with limited targeted therapies and poor clinical outcomes. Ferroptosis, an iron-dependent form of regulated cell death, plays a crucial role in tumor progression, metabolic reprogramming, and immune modulation. Increasing evidence suggests that dysregulation of ferroptosis contributes to therapeutic resistance and immune escape in various cancers. MYO19, a mitochondrial trafficking protein, has recently been implicated in oxidative stress and metabolic control, but its role in ferroptosis and tumor immunity remains unclear. Meanwhile, microRNAs (miRNAs) are recognized as key post-transcriptional regulators in cancer biology. Among them, hsa-miR-520a-3p has been reported to exhibit tumor-suppressive functions in several malignancies. However, the interplay between hsa-miR-520a-3p and MYO19, and their potential involvement in ferroptosis regulation and immune modulation in LUSC, has not been systematically investigated.MethodsData were collected from TCGA, UCSC XENA, ENCORI, HPA, and UALCAN public database. Differential expression, prognostic, correlation analyses and miRNA analyses were performed using bioinformatics tools including TIMER, TISIDB, Kaplan-Meier Plotter, and ENCORI. Ferroptosis-related analysis utilized Ze-Xian Liu’s dataset. Functional assays, including CCK-8 viability, Transwell migration, and MDA/GSH measurements, were performed in NCI-H226 and NCI-H2170 cells after transfection with miR-520a-3p mimics/inhibitors or MYO19 knockdown/overexpression constructs. Ferroptosis sensitivity was further tested under RSL3 treatment, and ferroptosis protein markers as well as rescue experiments were analyzed by Western blotting.ResultsThe result revealed that MYO19 was significantly upregulated in multiple tumor types and correlated with unfavorable prognosis. Especially in LUSC, elevated MYO19 expression was associated with advanced stage, reduced immune infiltration, and enrichment of ferroptosis-resistant transcriptional programs, whereas hsa-miR-520a-3p showed opposite patterns. Overexpression of hsa-miR-520a-3p in NCI-H226 and NCI-H2170 cells increased lipid peroxidation (MDA increased), reduced intracellular GSH, and enhanced RSL3-induced cytotoxicity, indicative of ferroptosis activation. Conversely, MYO19 knockdown elevated ACSL4 and reduced SLC7A11, changes that were partially reversed by MYO19 re-expression. These findings suggest that the hsa-miR-520a-3p/MYO19 axis is associated with ferroptosis susceptibility and may influence the immunosuppressive tumor microenvironment.